Pengaruh Kolonisasi Trichoderma spp. pada Akar Bibit Pisang terhadap Perkembangan Penyakit Layu Fusarium (Fusarium oxysporum f. sp. cubense) - Nurbailis, Nurbailis; Martinius, Martinius (Jurnal Natur Indonesia, 2011)
The purpose of the research was to obtain the superior Trichoderma that had ability to colonize root with the resultbeing effective to supress Fusarium wilt desease and promote banana seedling growth. This experiment consistedof 2 factors and 4 replications. The first factor was Trichoderma spp. namely : A. Trichoderma koningii strain S6sh(TK-S6sh), B Trichoderma viride strain T1sk (TV-T1sk) and Trichoderma harzianum strain S10sh (TH-S10sh). Thesecond factor was the kind of banana namely a.Cavendis, b. Barangan and c. Kepok. The observation werecolonization ability, Fusarium wilt desease development and the banana seedling growth. The result showed thatTV-T1sk was the best spesies to colonize all banana seedling root. The highest colonization in Barangan bananaseedling root reached 80%. Trichoderma colonization in banana seedling root could suppress Fusarium wilt diseasedevelopment and increase banana seedling weight. Higher ability of Trichoderma to colonize banana seedling rootcaused lower disease incidence of Fusarium wilt and greater biomass of banana seedling. Interaction betweenTV-T1Sk and Barangan banana was the best in colonization, so they were effective to suppress Fusarium wiltdesease and increase banana seedling biomass.